The effectiveness of an educational program in Islamic education using the flipped classroom strategies in developing the higher thinking skills in high school students in Jeddah - Bani Atta, Suhad Abdullah (Journal of Educational and Psychological Sciences, 2020)
The study aimed at designing an educational program using the flipped classroom strategies in the Hadith course, one of the branches of the Islamic education curriculum. And measuring its effectiveness in developing the higher thinking skills of high school students in Jeddah Governorate, and the study used the semi-experimental approach, and to achieve the objectives of the study, the researcher prepared an educational program in the modern course using the strategies of flipped classroom , and a test to measure higher thinking skills. It was applied to a sample of (48) female students of the second year of high school in the governorate of Jeddah for the academic year 2019/2020, where the experimental group reached (24) students. The control group (24) is also female. The results showed that the experimental group obtained a total average of (26.08 out of 30), in contrast to the control group obtaining a total average of (21.83 out of 30). The differences are statistically significant and in favor of the experimental, and in light of the results of the study, the researcher made recommendations and proposals that emphasized the need to use inverted separation strategies in the educational process because of their great impact on developing higher thinking skills.
Keywords: effective education; thinking skills; strategies; flipped classroom; Islamic education; secondary school